Regional and racial variations in the utilization of endoscopic retrograde cholangiopancreatography among pancreatic cancer patients in the United States. (14th May 2019) - Tavakkoli, Anna; Singal, Amit G.; Waljee, Akbar K.; Scheiman, James M.; Murphy, Caitlin C.; Pruitt, Sandi L.; Xuan, Lei; Kwon, Richard S.; Law, Ryan J.; Elta, Grace H.; Wright‐Slaughter, Phyllis; Valley, Thomas S.; et al.
Abstract: Background: Pancreatic cancer is projected to become the second leading cause of cancer‐related deaths by 2030. Endoscopic retrograde cholangiopancreatography (ERCP) is recommended as first‐line therapy for biliary decompression in pancreatic cancer. The aim of our study was to characterize geographic and racial/ethnic disparities in ERCP utilization among patients with pancreatic cancer. Methods: Retrospective cohort study using the US Surveillance, Epidemiology, and End Results (SEER)‐Medicare database to identify patients diagnosed with pancreatic cancer from 2003‐2013. The primary outcome was receipt of ERCP, with or without stent placement, vs any non‐ERCP biliary intervention. Results: Of the 36 619 patients with pancreatic cancer, 37.5% (n = 13 719) underwent an ERCP, percutaneous drainage, or surgical biliary bypass. The most common biliary intervention (82.6%) was ERCP. After adjusting for tumor location and stage, Blacks were significantly less likely to receive ERCP than Whites (aOR 0.84, 95% CI 0.72, 0.97) and more likely to receive percutaneous transhepatic biliary drainage (PTBD) (aOR 1.38, 95% CI 1.14, 1.66). Patients in the Southeast and the West were more likely to receive ERCP than those in the Northeast (Southeast aOR 1.21, 95% CI 1.04, 1.40; West aOR 1.16, 95% CI 1.01, 1.32). Conclusion: Racial/ethnic and geographic disparities in access to biliary interventions including ERCP exist for patients with pancreatic cancer in the United States. Our results highlight the need for further research and policies to improve access to appropriate biliary intervention for all patients. Abstract : To date, disparities in the receipt of endoscopic therapies among patients with pancreatic cancer have not been reported. The results from our study suggest that blacks with pancreatic cancer and patients in the Northeast region of the US are less likely to receive the gold standard therapy for obstructive jaundice.